Development and Characterization of Alkaline Phosphatase-Positive Human Umbilical Cord Perivascular Cells - Shun Nonoyama; Takeo Karakida; Risako Chiba-Ohkuma; Ryuji Yamamoto; Yuko Ujiie; Takatoshi Nagano; Yasuo Yamakoshi; Kazuhiro Gomi (Cells, 2021)
Human umbilical cord perivascular cells (HUCPVCs), harvested from human umbilical cord perivascular tissue, show potential for future use as an alternative to mesenchymal stromal cells. Here, we present the results for the characterization of the properties alkaline phosphatase-positive HUCPVCs (ALP(+)-HUCPVCs). These ALP(+)-HUCPVCs were created from HUCPVCs in this study by culturing in the presence of activated vitamin D3, an inhibitor of bone morphogenetic protein signaling and transforming growth factor-beta1 (TGF-β1). The morphological characteristics, cell proliferation, gene expression, and mineralization-inducing ability of ALP(+)-HUCPVCs were investigated at the morphological, biological, and genetic levels. ALP(+)-HUCPVCs possess high ALP gene expression and activity in cells and a slow rate of cell growth. The morphology of ALP(+)-HUCPVCs is fibroblast-like, with an increase in actin filaments containing alpha-smooth muscle actin. In addition to ALP expression, the gene expression levels of type I collagen, osteopontin, elastin, fibrillin-1, and cluster of differentiation 90 are increased in ALP(+)-HUCPVCs. ALP(+)-HUCPVCs do not have the ability to induce mineralization nodules, which may be due to the restriction of phosphate uptake into matrix vesicles. Moreover, ALP(+)-HUCPVCs may produce anti-mineralization substances. We conclude that ALP(+)-HUCPVCs induced from HUCPVCs by a TGF-β1 stimulation possess myofibroblast-like properties that have little mineralization-inducing ability.